Formulasi Trichoderma dan Mikoriza Arbuskular untuk Pengendalian Penyakit Busuk Pangkal Batang pada Kelapa Sawit: Formulation of Trichoderma sp. and Arbuscular Mycorrhiza to Control Basal Stem Rot Disease in Oil Palm - Sinthya E, Hana Christine; Khairani, Hagia Sophia; Sinaga, Meity Suradji; Toruan-Mathius, Nurita; Nawangsih, Abjad Asih (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2024)
Basal stem rot (G. boninense) is one of the most important diseases in oil palm. As biocontrol agents, Trichoderma spp. and arbuscular mycorrhizal fungi (AMF) have been reported to inhibit the growth of G. boninense. Nevertheless, the effectiveness of those biocontrol agents is unstable due to less appropriate formulation and application. Biofungicide formulation affects the effectiveness in controlling plant diseases, the ability to proliferate and survive in the environment, the period of storage, and reduces preparation time and application cost. This research aimed to develop the formulation of Trichoderma spp., and AMF to control G. boninense. Trichoderma spp. The active ingredient has been mass-produced in millet formulated with carriers: T1 using rice bran, while T3 was combined with rice bran and oil palm empty fruit bunches (EFB) compost. AMF active ingredient has been mass producted in shorgum root, and formulated with carrier, CMA1 using zeolite. While, CMA2 combined zeolite with EFB compost. AMF applications were on seed planting, Trichoderma spp. applications were on three months seedlings. Plant material used was DXP (76 × 36.11), which is susceptible to G. boninense. Disease progress was observed from latent period, disease incidence, disease severity, infection rate (r), area under disease progress curve (AUDPC), and the AMF-Trichoderma association with plant oil palm root. CMA2 and T3 formulation showed the best result to reduce disease severity and insidence. Therefore, CMA2 + T3 was the best combination of formulation for controlling oil palm basal stem rot disease based on disease progress.